The Effect of Systemic Methotrexate and Cyclosporine Combination Therapy inPsoriasis Vulgaris Patients in Bandung, Indonesia - Oki Suwarsa; Fatima Aulia Khairani; Syawalika Ulya Isneny; Erda Avriyanti; Hartati Purbo Dharmadji; Miranti Pangastuti; Endang Sutedja; Hendra Gunawan (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Methotrexate (MTX) and cyclosporine have been used as effective systemic mono-therapy for psoriasis. Several factors are considered to switch monotherapy to combination therapy because monotherapy is no longer effective and has higher side effects. Hence,clinicians have avoided systemic therapy combinations due to its toxicity. However, some studies showed that this combination therapy could be usedeffectively for psoriasis patients. Purpose: This study aimed to analyze the efficacy and adverse effects of systemic MTX and cyclosporine combination therapy in Indonesian psoriasis vulgaris patients. Methods: The retrospective study assessed the effectiveness of 3 monthsmono-therapyand combination therapy of systemic MTX and cyclosporine in psoriasisvulgaris patients from 2016–2017 in Dermatology Clinic, Dr. Hasan Sadikin Hospital, Bandung, West Java, Indonesia. Result: Psoriasis area and severity index (PASI) score 90 were achieved in the group MTX (50%) and cyclosporine group (50%), while none in the combination group.However, eight patients (50%) in group MTX and cyclosporine reached the primary endpoint of PASI 50. One patient in cyclosporine group had adverse effects on kidney profiles. Nonetheless, other patients had no biochemical changes. But, there was no significant difference in the change of PASI between each group (p=0.102). Conclusion: We propose that combination therapy of MTX and cyclosporine is relatively safe and efficacious in treating Indonesian psoriasis vulgaris patients. This combination treatment isas effective as MTX or cyclosporinemono-therapy.